1989
DOI: 10.1007/bf00716673
|View full text |Cite
|
Sign up to set email alerts
|

Vitrification and soluble carbohydrate levels inPetunia leaves as influenced by media gelrite and sucrose concentrations

Abstract: Normal nodal segments ofPetunia hybrida were grown on Murashige and Skoog salts containing varied levels of Gelrite and sucrose. Higher concentrations of Gelrite decreased vitrification while increased sucrose concentrations promoted vitrification. Leaves of vitreous plants had higher levels of reducing sugars and sucrose but lower or undetectable levels of inositol as compared to normal plants. Normal plants on medium void of inositol have the ability to synthesize inositol and maintain levels equal to that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 13 publications
2
18
0
2
Order By: Relevance
“…The aqueous upper phase containing the sugars was removed, transferred to a test tube, frozen in liquid N,, and lyophilized for at least 24 h. The sugars were derivatized as described by Ferguson et al (1979). Separation of silylated sugars by GC was essentially as described by Zimmerman and Cobb (1989). Plant Physiol.…”
Section: Analyses Of Organic Osmolytesmentioning
confidence: 99%
“…The aqueous upper phase containing the sugars was removed, transferred to a test tube, frozen in liquid N,, and lyophilized for at least 24 h. The sugars were derivatized as described by Ferguson et al (1979). Separation of silylated sugars by GC was essentially as described by Zimmerman and Cobb (1989). Plant Physiol.…”
Section: Analyses Of Organic Osmolytesmentioning
confidence: 99%
“…It has been widely reported that hyperhydricity of proliferating shoot cultures can be reduced by increasing the concentration of solidifying agents in the plant growth medium (Debergh et al 1981(Debergh et al , 1983Ghashghaie et al 1991;Selby et al 1989;Zimmerman & Cobb 1989). Hyperhydricity of mango somatic embryos can be reversed by increasing the gelling agent concentration of the plant growth medium.…”
Section: Discussionmentioning
confidence: 99%
“…Methods employed to combat hyperhydricity in gelled cultures have included modifi cations to the growth medium, such as increasing carbohydrate levels [ 93 ], modifying the concentration of gelling agents [ 86 ], and adding Bacto-peptone fractions [ 94 ] or agar hydrolysates [ 95 , 96 ]. Although these modifi cations can often alleviate symptoms they can also cause a simultaneous decrease in multiplication rates [ 97 ].…”
Section: The Control Of Hyperhydricitymentioning
confidence: 99%